Crime in England, 1550-1800
1 online resource.
Keywords: This volume, first published in 1977, brings together eleven studies of crime and the administration of the criminal law in England during the early modern period. They represent a variety of approaches - legal, historical and sociological - to the study of historical crime. The initial essay in this study, which is written from a legal standpoint, is the first coordinated account of the structure of criminal law administration in this formative period. It is followed by investigations into the nature and incidence of crime, court appearance and punishment, separate studies of witchcraft, infanticide and poaching, and an account of conditions in eighteenth-century Newgate. This book will be of particular interest to students of criminology and history.